Safety and Efficacy of Different Stent Strategies in Percutaneous Coronary Intervention - Waqas Ullah, MD, RPVI; Harigopal Sandhyavenu, MD; Syeda Ramsha Zaidi, MD; Mileydis Alonso, MD; Muhammad Atif Khan, MD; Irfan Ullah, MBBS; Farah Yasmin, MD; Aravind Reddy Polam, MD; Salman Zahid, MD; Arnav Kumar, MD, MSCR; Ewout W. Steyerberg, MSc, PhD; Mohammad Murtaza, MD; et al. (JACC: Advances)
Background: The utility of polymer-permanent, polymer-absorbable, and polymer-free drug-eluting stents (DES) in the context of different eluting drugs in patients undergoing percutaneous coronary intervention (PCI) remains controversial. Objectives: The purpose of this study was to compare the efficacy of different DES strategies in post-PCI patients. Methods: Digital databases were searched to select all randomized control trials. Different combinations of DES were directly compared with permanent-polymer sirolimus-eluting stents. The primary outcome was major adverse cardiovascular events; a composite of cardiovascular mortality, myocardial infarction (MI), and target vessel revascularization. A network meta-analysis was performed to determine the net relative risk (RR) and its 95% CI. Results: A total of 314 randomized control trials comprising 345,749 patients with coronary artery disease undergoing PCI were included. Compared with polymer-permanent sirolimus-eluting stent, polymer-free titanium-nitride-oxide (RR: 0.68; 95% CI: 0.53-0.87), polymer-permanent everolimus (RR: 0.89; 95% CI: 0.82-0.96), and zotarolimus stents (RR: 0.89; 95% CI: 0.79-0.99) had a lower risk of major adverse cardiovascular events at 5 years. Polymer-free titanium-nitride-oxide stents also had a significantly lower incidence of stent thrombosis (RR: 0.28; 95% CI: 0.13-0.59) and MI (RR: 0.41; 95% CI: 0.27-0.62) at 1 year. Bare metal stents had a significantly higher 1-year risk of MI (RR: 1.52; 95% CI: 1.25-1.86), and need for target vessel revascularization (RR: 2.26; 95% CI: 1.93-2.64). Conclusions: In comparison with polymer-permanent sirolimus, the newer stents including polymer-free titanium-nitride-oxide, polymer-permanent everolimus, and zotarolimus stents significantly reduce the risk of long-term ischemic events.